The effects of energy efficiency on GDP and GHG emissions in Germany - Marcus Jüppner; Anika Martin; Lucas Radke-Arden (Deutsche Bundesbank, 2024)
Energy efficiency improvements are a key component on the road towards a carbonneutral economy. We identify the development of energy efficiency in the data and show that in recent decades it has increased at the aggregate level. At the sectoral level, however, the development in energy efficiency was highly heterogenous. We, then, analyse the effects of exogenous improvements in energy saving technology by means of Environmental Multi-Sector Model EMuSe. According to the model, sustained exogenous gains in energy saving technology increase output while, at the same time, reduce emissions energy use and energy intensity. Thereby, they attenuate the model-implied negative co-movement of output and emissions that results from the introduction or an intensified increase of an emission price schedule. However, if energy efficiency evolves as during the last decades and the emission price follows the currently intended schedule in the national and EU-wide emissions trading system, the model predicts that the emissions reduction by 2030 set by the German Federal Climate Change Act cannot be met. It additionally requires a higher emission price or larger (exogenous) energy efficiency gains.
Keywords: 330